Investigating the Effects of Occupancy and Natural Ventilation on the Indoor Air Quality of Dormitories in Cold Regions - Irfan Nasir; Husnain Haider; Md. Shafiquzzaman; Majed Alinizzi; Guangji Hu; Abdul Razzaq Ghumman (Buildings)
Indoor air quality (IAQ) in higher education institutions’ dormitories, without mechanical ventilation, is a significant concern for students’ health due to prolonged occupancy in cold regions. The present investigation assessed IAQ by measuring two dormitories’ CO2, temperature, and relative humidity with the presence of one, two, three, and four occupants in the United Kingdom. Considering the possibility of natural ventilation by opening the windows in the summer, IAQ was monitored using two sensors located at 1 m and 2 m heights from the floor level of the dormitories in July. The tracer mass balance model showed close agreement with the monitored IAQ levels, with a direct relationship observed between occupant numbers and CO2 build-up. CO2 levels exceeded 1000 ppm within an hour during occupancy and closed ventilation, with air exchange rates between 0.12 and 0.2 h−1, increasing to 1334, 1259, 1884, and 2064 ppm after 30 min with one, two, three, and four occupants, respectively. Desired IAQ standards (1000 ppm) were achieved in 13, 33, 80, and 86 min for one, two, three, and four occupants after starting natural ventilation by opening 20% of the windows. The analysis of variance affirmed the effect of occupancy on IAQ, while the impact of height (1 m and 2 m) on CO2 levels was insignificant. This study underscores the need to effectively ventilate the partial opening of windows in dormitories to mitigate CO2 build-up, ensuring the desired ambient environment within dormitory rooms during summers in cold regions.